Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12955-018-0966-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the Quality of Life after Brain Injury (QOLIBRI) score: minor differences in patients with major versus no or mild traumatic brain injury at one-year follow up

Abstract: BackgroundThe Quality of Life after Brain Injury (QOLIBRI) score was developed to assess disease-specific health-related quality of life (HRQoL) after traumatic brain injury (TBI). So far, validation studies on the QOLIBRI were only conducted in cohorts with traumatic brain injury. This study investigated the longer-term residuals in severely injured patients, focusing specifically on the possible impact of major TBI.MethodsIn a prospective questionnaire investigation, 199 survivors with an injury severity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
2
22
1
Order By: Relevance
“…A head injury is associated with significant early limitations in most aspects of everyday life [49]. However, this phenomenon is also shown in other studies [50,51], in which the disease-specific health-related quality of life revealed no differences one year after a traumatic brain injury. This could be a result of recalibration, reconceptualization and reprioritization of internal standards and references utilized for selfappraisal, also called response shift [52].…”
Section: Discussionmentioning
confidence: 75%
“…A head injury is associated with significant early limitations in most aspects of everyday life [49]. However, this phenomenon is also shown in other studies [50,51], in which the disease-specific health-related quality of life revealed no differences one year after a traumatic brain injury. This could be a result of recalibration, reconceptualization and reprioritization of internal standards and references utilized for selfappraisal, also called response shift [52].…”
Section: Discussionmentioning
confidence: 75%
“…An alternative sensitivity analysis considered a lower utility value of 0.63 (in both treatment groups), based on the midpoint of mild and moderate TBI utility values, as reported in a Swiss quality of life study. 16 This was used to assess the impact of a lower utility estimate on the cost-effectiveness.…”
Section: Utilitymentioning
confidence: 99%
“…Additionally, electronic medical records were collected such as the clinical characteristics, treatment, and functional outcomes. After resuscitation, the GCS scores were categorized into mild TBI (GCS score [13][14][15], moderate TBI (GCS score 9-12), and severe TBI (GCS score 3-8). 4 The functional outcome of the present study was assessed using the GOS when the patients were discharged from hospital.…”
Section: Study Designs and Study Populationmentioning
confidence: 99%
“…HRQoL refers to the individual's perception of well-being in the physical, mental, and social domains. 13 The HRQoL is considered as one of the health outcome indicators, and various HRQoL measurement tools have been used to estimate TBI, such as the quality of life after brain injury overall scale (QOLIBRI-OS) 14,15 and the traumatic brain injury caregiver quality of life (TBI-CareQOL). 16 von Steinbuechel et al measured the HRQoL among 795 patients with TBI using QOLIBRI-OS and found that the extended Glasgow outcome scale (GOS-E) was associated with HRQoL, 14 while Born et al used this questionnaire and reported that severe head injury and injured extremities were associated with a poorer HRQoL.…”
mentioning
confidence: 99%